Wide band gap ZnMgO electro-optical film, optical micro-ring resonator and preparation method thereof
The Zn1-xMgxO film with wide bandgap was prepared by low-temperature radio frequency magnetron sputtering method, and an optical microring resonator was prepared in combination with the photon Damascus inlay process, which solved the problem of insufficient performance of film materials in the prior art, and achieved efficient ultraviolet-near-infrared band electro-optical modulation and low-loss optical microring resonator.
Patent Information
- Application Number
- CN202510044096.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art lacks thin film materials with wide bandgap and large electro-optical coefficients and their related photonic devices, making it difficult to achieve efficient development of photonic devices such as miniaturized ultraviolet-near-infrared band electro-optical modulators and optical switches.
Zn1-xMgxO (0.33≤x≤0.74) films with a-axis orientation, wide bandgap (3.97-5.33eV) and large bokehls electro-optical coefficient were prepared by low-temperature radio frequency magnetron sputtering method, and a c-axis preferentially oriented Zn1-xMgxO bar optical waveguide and optical microring resonator were prepared by photon Damascus damascus inlay process.
The high-quality growth of Zn1-xMgxO film and the low light transmission loss of optical microring resonators are achieved, which significantly improves the electro-optical modulation efficiency and device performance indicators.
Smart Images

Figure CN119877090A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nonlinear optical thin film materials and waveguide devices thereof, and in particular to Zn with large bandgap width (3.97-5.33 eV) and strong Pockels electro-optical effect. 1-x Mg x O (0.33≤x≤0.74) electro-optical film, optical microring resonator based on the film and preparation method thereof. Background Art
[0002] With the development of science and technology, photonic integrated circuits have shown great advantages in high-speed information processing. Electro-optic modulators are key devices in photonic integrated circuits. This device uses the electro-optical and other physical effects of materials to change the amplitude, phase, polarization and other parameters of light waves according to the laws of the external electric field, thereby realizing electrical control of optical signals. The principles of electro-optic modulation include Franz-Keldysh, Quantum Confined Stark, plasma dispersion and Pockels effects. The Pockels effect is based on the principle of electric field control of ion and electron polarization, which can achieve 10 -15 -10 -18 s-level ultrafast electro-optic modulation. The structure of the electro-optic modulator is divided into non-resonant type and resonant type according to the number of times the light passes through the modulation area. The non-resonant modulator, in which the light passes through the modulation area only once, is mainly a Mach-Zehnder structure, whose size is in the order of mm; the resonant modulator, in which the light passes through the modulation area multiple times, is mainly an optical micro-ring resonant cavity structure, whose size is in the order of μm.
[0003] Due to the ease of forming waveguide structures with strong light confinement and heterogeneous integration with mature microelectronic material platforms, the research and development of electro-optic thin film materials has received much attention from various countries. Organic polymers containing chromophore molecules have the advantage of large electro-optic coefficients, but their high-power light tolerance and heat resistance are relatively poor; ferroelectric films such as barium titanate and lead zirconate titanate have the characteristics of large electro-optic coefficients, but their dielectric constants are large (>100), resulting in high power consumption; wurtzite structure Al 1-x Sc x N and Zn 1-x Mg x O (ZnMgO) electro-optical film has the characteristics of large bandgap (≤6.2eV), small dielectric constant (<30), low optical transmission loss (<0.5dB / cm) and good compatibility with complementary metal oxide semiconductor (CMOS) process, and has unique advantages in ultraviolet band optical communication. Recently, a research team from Yale University in the United States reported that Al2O3 prepared by magnetron sputtering 0.9 Sc 0.1 N (bandgap width about 5.2eV) and Al0.7 Sc 0.3 N (bandgap width is about 4.0eV) along its c-axis direction electro-optic coefficient r 33 The effective electro-optic coefficient r c Up to 7.6±0.2pm / V Zn 0.72 Mg 0.28 O film (bandgap width is about 3.73eV). Summary of the invention
[0004] In view of the fact that there is still a lack of thin film materials with wide bandgap and large electro-optic coefficient and related photonic devices, the main purpose of the present invention is to provide a Zn with a bandgap width of 3.97-5.33 eV. 1-x Mg x O(0.33≤x≤0.74) electro-optical film, optical microring resonator on silicon based on the film and its preparation method are aimed at laying the material and device foundation for miniaturized ultraviolet-near-infrared electro-optical modulators and optical switches and other photonic devices.
[0005] The present invention has the following two technical features:
[0006] (1) Using low temperature (200-300℃) RF magnetron sputtering method to prepare Zn with a-axis orientation, wide bandgap (3.97-5.33eV), and large Pockels electro-optic coefficient 1-x Mg x O (0.33 ≤ x ≤ 0.74) film; specifically, when x = 0.33, r c and r 33 are 8.12±0.25pm / V and 5.28±0.16pm / V respectively; when x=0.35, r c and r 33 are 5.16±0.03pm / V and 3.36±0.20pm / V respectively; when x=0.55, r c and r 33 are 5.02±0.43 and 3.27±0.28 pm / V respectively; when x=0.74, r c and r 33 They are 3.07±0.37pm / V and 2.00±0.24pm / V respectively.
[0007] The existing technology mostly adopts molecular beam epitaxy (MBE), metal organic vapor deposition (MOCVD) or pulsed laser deposition (PLD) to prepare Zn with a-axis orientation and wide bandgap. 1-x Mg xO (0.33≤x≤0.56) thin film. The MBE method was used to prepare Zn with a-axis orientation and a bandgap of about 4.6eV at a growth temperature of 400°C. 0.44 Mg 0.56 O thin film. However, so far, no report or technical invention of the Pockels electro-optical properties of the film has been found. In addition, compared with these methods, the RF magnetron sputtering method has the advantages of simple growth process, large growth area and low cost.
[0008] (2) The c-axis preferentially oriented Zn was prepared by photon Damascus damascene process. 1-x Mg x O-strip optical waveguide and Zn 1- x Mg x O optical microring resonator, whose operating wavelength range is 250nm-2.5μm, covering a wide band from ultraviolet UVC to near infrared; specifically, the Zn 0.67 Mg 0.33 The optical transmission losses of the TE0 mode and TM0 mode of the O optical microring are approximately 2.52dB / cm and 2.74dB / cm, respectively.
[0009] The existing technology is to use dry or wet etching technology to prepare Zn 1-x Mg x O strip or ridge optical waveguide. 1- x Mg x O thin film is difficult to etch, and the roughness and slope or inclination of the waveguide sidewalls formed by these methods are large, resulting in large light transmission losses (>5dB / cm). Using the photonic Damascus inlay process, the ZnMgO strip optical waveguide and its optical microring resonator and other photonic devices are prepared by "first forming SiO2 grooves, then growing ZnMgO thin films inside them, and finally chemically and mechanically polishing the surface to form a smooth surface". Since SiO2 etching technology is very mature, it is easy to achieve smooth sidewalls and sidewall slopes close to 90o, which can achieve lower light transmission losses. In addition, the Zn prepared by the above-mentioned RF magnetron sputtering method 0.67 Mg 0.33 O film still grows in the SiO2 trench with preferred c-axis orientation. This helps to utilize the Pockels electro-optic coefficient in the c-axis direction. 1-x Mg x O material, the c-axis direction has the largest Pockels electro-optic coefficient tensor component r 33Although there are reports on the technology of preparing Si3N4 strip waveguide by photon damascene process, this technology uses low pressure chemical vapor deposition (LPCVD) and other methods to grow amorphous or polycrystalline Si3N4 thin film materials without Kerrs electro-optical effect in SiO2 grooves.
[0010] In order to achieve the above-mentioned objectives and technical features, the technical solution of the present invention is as follows:
[0011] First, Zn, which has a bandgap of 3.97–5.33 eV, 1-x Mg x The preparation method of the O (0.33≤x≤0.74) electro-optical film comprises the following steps:
[0012] Step A: Preparation of ZnMgO ceramic target;
[0013] Step B: substrate cleaning;
[0014] Step C: growing a ZnMgO thin film by radio frequency magnetron sputtering;
[0015] Step D: atmospheric heat treatment of the ZnMgO film.
[0016] Step A includes: the ZnMgO ceramic target includes a ZnMgO ceramic target for growing a wide bandgap Zn 1-x Mg x Ceramic target and ZnO(0.33≤x≤0.74) thin film 0.79 Mg 0.21 O buffer layer ceramic target; specifically, the two ceramic targets are made by weighing raw materials according to a specific component ratio. The method for making the ceramic target includes: using ZnO with a purity of 99.99% and MgO with a purity of 99.99% as raw materials, and making the target material according to the weight percentage of 91.6%-38.68%: 18.4%-61.32%; Zn 0.79 Mg 0.21 The method for manufacturing an O buffer layer ceramic target comprises: using ZnO with a purity of 99.99% and MgO with a purity of 99.99% as raw materials, and manufacturing a target material according to a weight percentage of 89%:11%.
[0017] Step B includes: placing the R-surface Al2O3 substrate upright in a customized cleaning rack, ultrasonically cleaning it in acetone, alcohol and pure water for 10 minutes each; then, using a nitrogen gun to blow dry the substrate; finally, placing it in an oven and keeping it at 120°C for 30 minutes.
[0018] Step C includes: the process parameters of the RF magnetron co-sputtering technology include: when the background vacuum is reduced to 7.4×10 -7When the pressure is below 300°C, a mixed gas of O2 and Ar is introduced into the growth chamber, the Ar / (Ar+O2) gas ratio is 50%-75%, the flow rate range is 5-10sccm, the substrate temperature range is 200-300°C, the gas pressure range is 2-5mTorr, the RF power range of the ceramic target is 100-150W, the distance between the target and the sample range is 100-150mm, and the substrate rotation speed range is 15-30rpm.
[0019] Step D includes: placing the grown film sample into a heat treatment furnace, increasing the temperature from room temperature to a maximum temperature of 500-600°C at a rate of 15°C / min, keeping the temperature for 1-4 hours, and cooling with the furnace after keeping the temperature.
[0020] Secondly, based on the Zn 1-x Mg x The preparation method of an optical microring resonator of an O (0.33≤x≤0.74) electro-optical film comprises the following steps:
[0021] Step A, optical microring resonator layout design and fabrication;
[0022] Step B, SiO2 (thickness about 5 microns) / Si substrate cleaning;
[0023] Step C, growing an amorphous Si mask;
[0024] Step D, preparing electron beam gel and pre-baking;
[0025] Step E, electron beam exposure, development, and post-baking;
[0026] Step F, dry etching amorphous Si and SiO2 to form SiO2 grooves of a certain depth on the surface of the substrate;
[0027] Step G, removing the amorphous Si mask and cleaning the substrate;
[0028] Step H, using a radio frequency magnetron sputtering method to grow a c-axis preferentially oriented wide bandgap ZnMgO electro-optical film in the SiO2 groove;
[0029] Step I: forming a smooth surface on the substrate surface through chemical mechanical polishing (CMP).
[0030] Step J, growing a SiO2 upper confinement layer;
[0031] Step K, spin coating photoresist and pre-baking;
[0032] Step L, photolithography, development, and post-baking;
[0033] Step M, deep etching of the SiO2 upper limiting layer and Si;
[0034] Step N, removing the residual photoresist on the surface, cleaning the substrate and then scribing to form discrete ZnMgO optical microring resonators.
[0035] Step A includes: first, according to the target resonant wavelength of the device and the refractive index of the ZnMgO material, the width and height of the waveguide core layer that can achieve single-mode transmission at the wavelength are determined. Then, according to the desired free spectral range (FSR) and taking into account the possible process errors, different microring radii (R) and bus waveguide-microring spacing (G) values are designed. Finally, the electronic layout of the optical microring resonator array with different R and G is produced using dedicated software.
[0036] Step B includes: placing a Si substrate with a surface thermal oxide layer (thickness of about 5 microns) (referred to as SiO2 / Si substrate) into a customized cleaning rack, and ultrasonically cleaning it in acetone, alcohol and pure water for 10 minutes each; then, using a nitrogen gun to blow dry the surface of the substrate; finally, placing it in an oven and keeping it at 120°C for 30 minutes.
[0037] Step C includes: growing an amorphous Si mask of a certain thickness on the above SiO2 / Si substrate by a plasma enhanced chemical vapor deposition (PECVD) method.
[0038] Step D comprises: spin coating a certain thickness of electron beam glue on the substrate at a rotation speed of 4000-6000 rpm. After coating, the sample is placed on a hot plate for baking at a certain temperature and time to stabilize the performance of the electron beam glue.
[0039] Step E includes: placing the sample in an electron beam exposure device and evacuating the sample until the background vacuum is reduced to 4×10 -4 Pa or less. After establishing the sample coordinate system, writing field alignment and setting exposure parameters, the exposure begins. After the exposure is completed, the sample is taken out and developed. The exposed area is removed due to the increased solubility, leaving the unexposed photoresist as a mask. After development, the sample is placed on a hot plate and baked at a certain temperature and time to further solidify the electron beam glue and reduce the impact of moisture on subsequent processing.
[0040] Step F includes: first, using the reactive ion etching (RIE) method to etch amorphous Si to a certain depth along the electron beam mask window to form a mask window for etching SiO2 thereunder; then, further using the RIE method to etch SiO2 to a certain depth along the amorphous Si mask window.
[0041] Step G includes: soaking the sample in acetone for a period of time to remove the electron beam glue remaining on the surface; then, soaking the sample in a potassium hydroxide solution with a concentration of about 20% for a certain period of time to remove the amorphous Si mask remaining on the surface; finally, rinsing in pure water and ultrapure water for 1 minute each, using a nitrogen gun to blow dry the substrate surface, and drying at 120°C for 30 minutes. After this step, a certain depth of SiO2 grooves are formed on the surface of the SiO2 / Si substrate.
[0042] Step H comprises: using the steps shown in Example 1 of the present invention, successively growing Zn with a thickness ranging from 50 to 100 nm 0.79 Mg 0.21 O buffer layer and a wide bandgap ZnMgO electro-optical film whose thickness exceeds the depth of the SiO2 trench.
[0043] Step I comprises: using a polishing liquid with a pH value of 5.55-6.46, performing chemical mechanical polishing for a certain period of time under the conditions of a pressure range of 300-500g, a rotation speed range of 20-30rpm and a thinning rate of 30-60nm / min, removing the ZnMgO electro-optical film except in the SiO2 groove, and forming a smooth surface with a sub-nanometer root mean square roughness. Then, rinsing in acetone, alcohol and pure water for 1 minute each, blowing the substrate surface dry with a nitrogen gun, and drying at 120°C for 30 minutes.
[0044] Step J includes: using the PECVD method to grow a SiO2 upper confinement layer with a thickness of about 2000 nm on the surface of the sample after CMP treatment.
[0045] Step K includes: spin coating a photoresist of about 7 μm on the surface of the sample at a rotation speed of about 3000 rpm. After coating, the sample is placed on a hot plate and baked at a certain temperature and time to stabilize the performance of the photoresist.
[0046] Step L includes: using a designed device separation photomask and a UV lithography machine for exposure, and then, through development and post-baking, obtaining a solidified photoresist mask.
[0047] Step M includes: using the RIE method to etch SiO2 downward along the photoresist window to a depth of about 5 μm; then, further using the RIE method to etch Si downward to a depth of about 100 μm.
[0048] Step N includes: soaking the sample in acetone for a period of time to remove the photoresist remaining on the surface; then, rinsing in acetone, alcohol and pure water for 1 minute each, using a nitrogen gun to blow dry the substrate surface, and drying at 120° C. for 30 minutes; finally, using a dicing machine to scribe along the scribe lines formed on the substrate surface after step M to obtain discrete ZnMgO optical microring resonator devices.
[0049] It can be seen from the above technical solution that the wide bandgap Zn 1-x Mg x O(0.33≤x≤0.74) electro-optical film, optical microring resonator and preparation method thereof have at least one or part of the following beneficial effects:
[0050] (1) Zn with a bandgap of 3.97 eV 0.67 Mg 0.33 The electro-optic coefficient of the O film along the c-axis direction r c and r 33 They reach 8.12±0.25pm / V and 5.28±0.16pm / V respectively. 33 The value is similar to the bandgap width Al 0.7 Sc 0.3 It is more than 2.1 times that of N electro-optical film (2.07pm / V).
[0051] (2) Zn 0.45 Mg 0.55 (bandgap 4.12eV) and Zn 0.26 Mg 0.74 The electro-optic coefficient r of O film (bandgap 5.33 eV) 33 Reach 3.27±0.28pm / V and 2.00±0.24pm / V respectively. 0.26 Mg 0.74 O thin film 33 Larger than Al, which has a bandgap of about 5.2 eV 0.9 Sc 0.1 The r of N film 33 (1.32±0.43pm / V).
[0052] (3) Zn with a radius of 201.5 μm 0.67 Mg 0.33 The intrinsic quality factors (Q0) of the TE0 mode and TM0 mode of the optical microring resonator at 1.55 μm are approximately 1.18×10 5 and 1.08×10 5 , and using Al with a similar bandgap width 0.7 Sc 0.3 Optical microring resonator made of N electro-optical thin film (Q0≈3.6×10 4 ) is one order of magnitude higher.
[0053] (4) Using Zn 0.79 Mg 0.21 The O buffer layer not only effectively suppresses the wide bandgap Zn 1-x Mg xThe phase separation between cubic MgO and wurtzite ZnO in the electro-optical film of O(0.33≤x≤0.74) significantly increases the 1-x Mg x Growth quality of O(0.33≤x≤0.74) electro-optical films on SiO2 / Si. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 . In the embodiment of the present invention, Zn 1-x Mg x Flow chart of the preparation method of O(0.33≤x≤0.74) electro-optical film.
[0055] Figure 2 . Zn prepared in Example 1 of the present invention 0.67 Mg 0.33 (a) XRD 2θ-ω scanning spectrum, (b) Tauc curve, (c) electro-optic modulation amplitude and (d) modulation intensity of ZnO thin film as a function of analysis angle. The inset in (a) is the rocking curve spectrum of ZnO (110) crystal plane. In (a), S, Z and M represent the substrate Al2O3, ZnO and MgO, respectively. The solid line and dashed line in (b) are the experimental and fitting values, respectively.
[0056] Figure 3 . Zn prepared in Examples 2-4 of the present invention 1-x Mg x (a) XRD 2θ-ω scanning spectrum of ZnO film, (b) rocking curve spectrum of ZnO (110) crystal plane. In (a), S, Z and M represent the substrate Al2O3, ZnO and MgO respectively. The solid line and dashed line in (b) are the experimental and fitting values respectively.
[0057] Figure 4 . Zn prepared in Examples 2-4 of the present invention 1-x Mg x (a) Transmittance curve of O film, (b) cathode luminescence spectrum. The peaks marked by letters AD in (b) are 232.7nm, 301.6nm, 333.9nm and 381.2nm respectively.
[0058] Figure 5 . Schematic diagram of the process flow of the ZnMgO optical microring resonator of Example 5 of the present invention.
[0059] Figure 6 .Electron beam exposure layout of the ZnMgO microring resonator device designed in Example 5 of the present invention. (a) Overall layout, (b) R = 100.75 μm microring resonator unit, (c) R = 201.5 μm microring resonator unit, (d) R = 302.25 μm microring resonator unit, (e) alignment mark and (f) wedge couplers at both ends of the bus waveguide.
[0060] Figure 7 . Zn grown on SiO2 / Si substrate in Example 5 of the present invention 0.67 Mg 0.33 XRD 2θ-ω scanning spectrum of ZnO thin film. The inset is the rocking curve spectrum of ZnO(002) crystal plane.
[0061] Figure 8 . In Example 5 of the present invention, Zn before and after CMP treatment 0.67 Mg 0.33 AFM images of the O film surface. (a) Before CMP treatment and (b) after CMP treatment.
[0062] Fig. 9 .Images of the ZnMgO microring resonant device prepared in Example 5 of the present invention. (a) Optical microscope photo of SiO2 grooves on SiO2 / Si substrate before growing ZnMgO film, (b) Scanning electron microscope (SEM) photo of the end face of the wedge coupler of the device, (c) SEM photo of the cross section of the microring and the adjacent bus waveguide after growing ZnMgO film, and (d) Transmission electron microscope selected area electron diffraction image of the ZnMgO film in the SiO2 grooves.
[0063] Fig.10 .Performance parameters of the ZnMgO microring resonator prepared in Example 5 of the present invention. (a) Transmission spectrum of R = 100.75 μm microring resonator, (b) Transmission spectrum of R = 201.5 μm microring resonator, (c) Transmission spectrum of R = 302.25 μm microring resonator, (d) TE0 mode resonance peak of R = 201.5 μm microring resonator, (e) TM0 mode resonance peak of R = 201.5 μm microring resonator, (f) Change of the energy coupling coefficient between the bus band and the microring of R = 201.5 μm microring resonator with the coupling gap G. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical features and technical solutions of the present invention more clearly understood, the present invention is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings. It should be noted that the specific embodiments below are only for illustration and are not intended to limit the present invention.
[0065] Embodiment 1:
[0066] like Figure 1 As shown, the preparation method of this embodiment includes:
[0067] Step A, weigh the raw materials according to the component ratio shown in Table 1, and prepare the raw materials for growing Zn 0.67 Mg 0.33 O ceramic target for electro-optical thin films.
[0068] Table 1. Used for growing Zn 0.67 Mg 0.33 O Target composition of electro-optical thin films
[0069] raw material purity Molar mass Weight Percent ZnO 99.99% 81.39 81.6% MgO 99.99% 40.3 18.4%
[0070] Step B: Place the R-surface Al2O3 substrate upright in a customized cleaning rack and ultrasonically clean it in acetone, alcohol and pure water for 10 minutes each; then, use a nitrogen gun to blow dry the substrate surface; finally, place it in an oven and keep it at 120°C for 30 minutes.
[0071] Step C includes the following sub-steps:
[0072] Sub-step C1: Place the cleaned substrate into the sample holder. Evacuate the sample holder until the background vacuum is less than 7.4×10 -7 Torr. Set the equipment parameters according to the values shown in Table 2.
[0073] Table 2. Magnetron sputtering equipment setting parameters
[0074] Thin film layer Substrate temperature Air pressure Target RF power Ar flow <![CDATA[O2 flow rate]]> Target to sample distance Substrate rotation speed <![CDATA[Zn 0.67 Mg 0.33 O]]> 300℃ 3mTorr 120W 6sccm 6sccm 150mm 20rpm
[0075] Sub-step C2, when the substrate temperature is stabilized at 300 degrees, pre-sputtering the ZnMgO ceramic target for 10 minutes.
[0076] Sub-step C3, adjust the target position to the ZnMgO ceramic target position. Open the substrate baffle and start growth. When the expected growth time is reached, immediately close the substrate baffle. Turn off the substrate heating device. When the substrate temperature drops below 100 degrees, move the substrate out of the growth chamber.
[0077] Step D: Heat treatment: The grown thin film sample is placed in a heat treatment furnace, and the temperature is increased from room temperature to 600°C at a rate of 15°C / min, and kept at 600°C for 2 hours, and then cooled in the furnace.
[0078] Figure 2 Demonstrating the Zn prepared in Example 1 of the present invention 0.67 Mg 0.33 Structural, optical and electro-optical properties of O films. Figure 2 (a) is the X-ray diffraction (XRD) spectrum. The film only shows the diffraction peak of the ZnO (110) crystal plane, reflecting a good a-axis orientation. The film and the R-face Al2O3 substrate have the following epitaxial relationship: ZnO (110) || Al2O3 (024), and As shown in the inset of Figure (a), the half-width of the rocking curve of the (110) crystal plane of the film is 0.65°, indicating that it has good crystalline quality. Figure 2As shown in (b), the linear part of the Tauc curve is extended to intersect with the x-axis, and the optical bandgap width of the film is obtained to be 3.97 eV.
[0079] The effective electro-optic coefficient (r c ). According to the above epitaxial relationship, electron beam evaporation was used to deposit Zn 0.67 Mg 0.33 A pair of platinum electrodes (thickness of about 50 nm) with a spacing of 150 μm were prepared on the surface of the O film along its in-plane c-axis, i.e., the
[001] crystal direction. A linearly polarized 632.8 nm wavelength He-Ne laser was used to pass through the center of the platinum electrode pair, and its linear polarization direction was the same as that of the Zn 0.67 Mg 0.33 The c-axis angle in the O film plane is 45°. A 20-150V AC voltage (frequency 1kHz) is applied to the platinum electrode pair through a metal probe. The modulation amplitude and phase of the transmitted light are collected using a photodetector connected to a phase-locked amplifier. Figure 2 As shown in (c), the modulation amplitude varies with the applied alternating electric field (E AC ) increases linearly, proving that the Pockels or linear electro-optical effect occurs. Figure 2 As shown in (d), there is a 45° analysis angle difference between the modulation intensity and the absolute intensity, which further confirms that it has the Pockels electro-optical effect. 0.67 Mg 0.33 The refractive index (n1) of the
[001] direction in the O film plane and The crystal refractive index (n3) is approximately equal to r 33 / r 13 The ratio is -1.86. Then, using formulas (1) and (2), we can get the film along the c-axis direction r c and r 33 They are 8.12±0.25pm / V and 5.28±0.16pm / V respectively. 33 The value is similar to the bandgap width Al 0.7 Sc 0.3 It is more than 2.1 times that of N electro-optical film (2.07pm / V).
[0080]
[0081] Among them I m , I c , n and d are the transmitted light modulation intensity, the transmitted light absolute intensity, the film refractive index and the film thickness, respectively.
[0082] Embodiment 2:
[0083] Step A, weigh the raw materials according to the component ratios shown in Table 3 and Table 4, and prepare the raw materials for growing Zn 0.65 Mg0.35 Ceramic targets for growing ZnO electro-optical thin films and 0.79 Mg 0.21 O buffer layer of ceramic target.
[0084] Table 3. Used for growing wide bandgap Zn 0.65 Mg 0.35 O Target composition of electro-optical thin films
[0085] raw material purity Molar mass Weight Percent ZnO 99.99% 81.39 60.67% MgO 99.99% 40.3 39.33%
[0086] Table 4. Used for growing Zn 0.79 Mg 0.21 O buffer layer target composition
[0087] raw material purity Molar mass Weight Percent ZnO 99.99% 81.39 89% MgO 99.99% 40.3 11%
[0088] Step B: Place the R-surface Al2O3 substrate upright in a customized cleaning rack and ultrasonically clean it in acetone, alcohol and pure water for 10 minutes each; then, use a nitrogen gun to blow dry the substrate surface; finally, place it in an oven and keep it at 120°C for 30 minutes.
[0089] Step C includes the following sub-steps:
[0090] Sub-step C1: Place the cleaned substrate into the sample holder. Evacuate the sample holder until the background vacuum is less than 7.4×10 -7 Torr. Set the equipment parameters according to the values shown in Table 5.
[0091] Table 5. Magnetron sputtering equipment setting parameters
[0092] Thin film layer Substrate temperature Air pressure Target RF power Ar flow <![CDATA[O2 flow rate]]> Target to sample distance Substrate rotation speed <![CDATA[Zn 0.79 Mg 0.21 O]]> 300℃ 3mTorr 100W 6sccm 6sccm 150mm 20rpm <![CDATA[Zn 0.65 Mg 0.35 O]]> 300℃ 3mTorr 120W 6sccm 6sccm 150mm 20rpm
[0093] Sub-step C2, when the substrate temperature is stabilized at 300 degrees, pre-sputter the two ceramic targets for 10 minutes respectively.
[0094] Sub-step C3, adjust the target position to the low Mg component target position, open the substrate shutter, and start growth. When the expected growth time is reached, immediately close the substrate shutter.
[0095] Sub-step C4, adjust the target position to the high Mg component target position. Open the substrate baffle and start growth. When the expected growth time is reached, immediately close the substrate baffle. Turn off the substrate heating device. When the substrate temperature drops below 100 degrees, move the substrate out of the growth chamber.
[0096] Step D: Heat treatment: The grown thin film sample is placed in a heat treatment furnace, and the temperature is increased from room temperature to 600°C at a rate of 15°C / min, and kept at 600°C for 2 hours, and then cooled in the furnace.
[0097] Embodiment 3:
[0098] Step A, weigh the raw materials according to the component ratios shown in Table 6 and Table 7, and prepare the raw materials for growing Zn 0.45 Mg 0.55 Ceramic targets for growing ZnO thin films and 0.79 Mg 0.21 O buffer layer of ceramic target.
[0099] Table 6. Used for growing wide bandgap Zn 0.45 Mg 0.55 O Target composition of electro-optical thin films
[0100] raw material purity Molar mass Weight Percent ZnO 99.99% 81.39 60.67% MgO 99.99% 40.3 39.33%
[0101] Table 7. For growing Zn 0.79 Mg 0.21 O buffer layer target composition
[0102] raw material purity Molar mass Weight Percent ZnO 99.99% 81.39 89% MgO 99.99% 40.3 11%
[0103] Step B: Place the R-surface Al2O3 substrate upright in a customized cleaning rack and ultrasonically clean it in acetone, alcohol and pure water for 10 minutes each; then, use a nitrogen gun to blow dry the substrate surface; finally, place it in an oven and keep it at 120°C for 30 minutes.
[0104] Step C includes the following sub-steps:
[0105] Sub-step C1: Place the cleaned substrate into the sample holder. Evacuate the sample holder until the background vacuum is less than 7.4×10 -7 Torr. Set the equipment parameters according to the values shown in Table 8.
[0106] Table 8. Magnetron sputtering equipment setting parameters
[0107] Thin film layer Substrate temperature Air pressure Target RF power Ar flow <![CDATA[O2 flow rate]]> Target to sample distance Substrate rotation speed <![CDATA[Zn 0.79 Mg 0.21 O]]> 300℃ 3mTorr 100W 6sccm 6sccm 150mm 20rpm <![CDATA[Zn 0.45 Mg 0.55 O]]> 300℃ 3mTorr 120W 6sccm 6sccm 150mm 20rpm
[0108] Sub-step C2, when the substrate temperature is stabilized at 300 degrees, pre-sputter the two ceramic targets for 10 minutes respectively.
[0109] Sub-step C3, adjust the target position to the low Mg component target position, open the substrate shutter, and start growth. When the expected growth time is reached, immediately close the substrate shutter.
[0110] Sub-step C4, adjust the target position to the high Mg component target position. Open the substrate baffle and start growth. When the expected growth time is reached, immediately close the substrate baffle. Turn off the substrate heating device. When the substrate temperature drops below 100 degrees, move the substrate out of the growth chamber.
[0111] Step D: Heat treatment: The grown thin film sample is placed in a heat treatment furnace, and the temperature is increased from room temperature to 600°C at a rate of 15°C / min, and kept at 600°C for 2 hours, and then cooled in the furnace.
[0112] Embodiment 4:
[0113] Step A, weigh the raw materials according to the component ratios shown in Table 9 and Table 10, and prepare the raw materials for growing Zn 0.26 Mg 0.74 Ceramic targets for growing ZnO thin films and 0.79 Mg 0.21 O buffer layer of ceramic target.
[0114] Table 9. Used for growing wide bandgap Zn 0.26 Mg 0.74 O Target composition of electro-optical thin films
[0115]
[0116]
[0117] Table 10. For growing Zn 0.79 Mg 0.21 O buffer layer target composition
[0118] raw material purity Molar mass Weight Percent ZnO 99.99% 81.39 89% MgO 99.99% 40.3 11%
[0119] Step B: Place the R-surface Al2O3 substrate upright in a customized cleaning rack and ultrasonically clean it in acetone, alcohol and pure water for 10 minutes each; then, use a nitrogen gun to blow dry the substrate surface; finally, place it in an oven and keep it at 120°C for 30 minutes.
[0120] Table 11. Magnetron sputtering equipment setting parameters
[0121] Thin film layer Substrate temperature Air pressure Target RF power Ar flow <![CDATA[O2 flow rate]]> Target to sample distance Substrate rotation speed <![CDATA[Zn 0.79 Mg 0.21 O]]> 300℃ 3mTorr 100W 6sccm 6sccm 150mm 20rpm <![CDATA[Zn 0.26 Mg 0.74 O]]> 300℃ 3mTorr 120W 6sccm 6sccm 150mm 20rpm
[0122] Step C includes the following sub-steps:
[0123] Sub-step C1: Place the cleaned substrate into the sample holder. Evacuate the sample holder until the background vacuum is less than 7.4×10 -7 Torr. Set the equipment parameters according to the values shown in Table 11.
[0124] Sub-step C2, when the substrate temperature is stabilized at 300 degrees, pre-sputter the two ceramic targets for 10 minutes respectively.
[0125] Sub-step C3, adjust the target position to the low Mg component target position, open the substrate shutter, and start growth. When the expected growth time is reached, immediately close the substrate shutter.
[0126] Sub-step C4, adjust the target position to the high Mg component target position. Open the substrate baffle and start growth. When the expected growth time is reached, immediately close the substrate baffle. Turn off the substrate heating device. When the substrate temperature drops below 100 degrees, move the substrate out of the growth chamber.
[0127] Step D: Heat treatment: The grown thin film sample is placed in a heat treatment furnace, and the temperature is increased from room temperature to 600°C at a rate of 15°C / min, and kept at 600°C for 2 hours, and then cooled in the furnace.
[0128] Figure 3 The Zn prepared in Example 2-4 of the present invention 1-x Mg x XRD pattern of O film. Figure 3 As shown in (a), without a buffer layer, Zn 0.65 Mg 0.35 O film only shows the diffraction peak of MgO(200) crystal plane, indicating that its crystal structure is cubic. 0.79 Mg 0.21 O buffer layer, Zn 1-x Mg x The ZnO(0.35≤x≤0.74) film only shows the ZnO(110) crystal plane diffraction peak, which shows a good a-axis orientation. 0.79 Mg 0.21 The O buffer layer effectively inhibits the formation of the cubic phase. Figure 3 As shown in (b), Zn 0.65 Mg 0.35 O, Zn 0.45 Mg 0.55 O and Zn 0.26 Mg 0.74 The half-height widths of the rocking curves of the (110) crystal plane of the O film are 1.24°, 1.05°, and 1.11°, respectively. Compared with the films of similar composition prepared by the same method that have been reported in the literature, the half-height widths are smaller, indicating that it has good crystal quality.
[0129] Figure 4 The Zn prepared in Example 2-4 of the present invention 1-x Mg x Transmittance curve and cathode luminescence spectrum of O film. Figure 4 As shown in (a), without a buffer layer, Zn 0.65 Mg 0.35 O film shows very high transmittance in the 230-380nm UV band, further confirming the formation of cubic phase. 0.79 Mg 0.21 O buffer layer, Zn 1-x Mg xThe transmittance of O(0.35≤x≤0.74) film in the ultraviolet band of 230-300nm is significantly reduced. 0.65 Mg 0.35 Compared with ZnO thin films, 0.45 Mg 0.55 O and Zn 0.26 Mg 0.74 O has a higher transmittance (about 10%) at 230-300nm. This indicates that Zn 0.45 Mg 0.55 O and Zn 0.26 Mg 0.74 There is a certain amount of cubic phase in the O film, which indicates the phase separation between cubic phase and wurtzite. 0.65 Mg 0.35 Compared with O, the absorption cutoff edge of the wurtzite phase of the two films moves toward the shorter wavelength direction, indicating that it has a larger bandgap. Figure 4 As shown in (b), the cathode luminescence spectrum (CL) test shows that Zn 0.45 Mg 0.55 The film shows two characteristic peaks centered at 301.6nm and 333.9nm, with corresponding bandgap widths of 4.11eV and 3.71eV, respectively. 0.45 Mg 0.55 Thin films and Zn 0.79 Mg 0.21 O buffer layer has a band gap. Zn 0.26 Mg 0.74 The O film shows two other characteristic peaks centered at 232.7nm and 381.2nm, with corresponding bandgap widths of 5.33eV and 3.25eV, respectively. These two values should be the bandgap widths of cubic ZnMgO and wurtzite ZnO, further confirming the occurrence of phase separation.
[0130] The same method and formula as in Example 1 were used to determine the Zn prepared in Examples 2-4. 1-x Mg x As shown in Table 12, as the Mg content increases, the electro-optic modulation amplitude per unit film thickness gradually decreases. 0.65 Mg 0.35 O, Zn 0.45 Mg 0.55 and Zn 0.26 Mg 0.74 The effective electro-optic coefficient r of the O film along the c-axis c They reach 5.16±0.03pm / V, 5.02±0.43pm / V and 3.07±0.37pm / V respectively. 0.65Mg 0.35 O, Zn 0.45 Mg 0.55 and Zn 0.26 Mg 0.74 The electro-optic coefficient r of the O film along the c-axis 33 They reach 3.36±0.20pm / V, 3.27±0.28pm / V and 2.00±0.24pm / V respectively. Zn has a bandgap width of 5.33eV 0.26 Mg 0.74 O thin film 33 Larger than Al, which has a bandgap of about 5.2 eV 0.9 Sc 0.1 The r of N film 33 (1.32±0.43pm / V). This indicates that the use of Zn 1-x Mg x O(0.35≤x≤0.74) electro-optical film will significantly improve the electro-optical modulation efficiency in the ultraviolet band.
[0131] Table 12. Zn prepared in Examples 2-4 of the present invention 1-x Mg x Electro-optical parameters of O(0.35≤x≤0.74) films
[0132] x Thickness(nm) <![CDATA[I m ]]> <![CDATA[I c ]]> Modulation Amplitude <![CDATA[r c (pm / V)]]> <![CDATA[r 33 (pm / V)]]> 0.35 225.0 8.82E-08 0.055376 1.59E-06 5.16±0.03 3.36±0.20 0.55 259.3 9.15E-08 0.055035 1.66E-06 5.02±0.43 3.27±0.28 0.74 216.8 7.90E-08 0.064974 1.22E-06 3.07±0.37 2.00±0.24
[0133] Note: I m and I c are the transmitted light modulation intensity and absolute intensity, respectively.
[0134] Embodiment 5:
[0135] According to Figure 5 The process method shown is to prepare Zn-based 0.67 Mg 0.33 The preparation method of this embodiment includes:
[0136] Step A, first, according to the device resonant wavelength 1.55μm and Zn 0.67 Mg 0.33 The refractive index of the electro-optic film (about 1.82) and other parameters determine that the width and height of the waveguide core layer that can achieve single-mode transmission at a wavelength of 1.55 μm are 2250 nm and 850 nm respectively. In the optical microring resonator composed of a single bus waveguide and a single microring, the light transmitted in the bus waveguide can only be coupled into the microring resonator and resonantly enhanced if the phase matching condition shown in equation (1) is met.
[0137] m×λ=n eff×L (1) where m is the resonance order, λ is the operating wavelength, and n eff is the effective refractive index of the waveguide, and L is the circumference of the microring. Then, according to the above conditions and the desired free spectral range (FSR), and taking into account the possible process errors, different microring radius (R) and bus waveguide-microring spacing (G) values are designed. Finally, Klayout and other software are used to make the electronic layout of the optical microring resonator array with different R and G.
[0138] In step B, a Si substrate with a surface thermal oxide layer (thickness of about 5 microns) (referred to as SiO2 / Si substrate) is placed in a customized cleaning rack and ultrasonically cleaned in acetone, alcohol and pure water for 10 minutes each; then, the substrate surface is blown dry using a nitrogen gun; finally, it is placed in an oven and kept at 120°C for 30 minutes.
[0139] Step C: growing an amorphous Si mask with a thickness of about 400 nm on the above SiO2 / Si substrate by a plasma enhanced chemical vapor deposition (PECVD) method.
[0140] Step D, spin coating the electron beam glue with a thickness of about 400 nm on the substrate at a rotation speed of about 4000 rpm. After coating, the sample is placed on a hot plate and baked at a certain temperature and time to stabilize the performance of the electron beam glue.
[0141] Step E: Place the sample in the electron beam exposure equipment and evacuate until the background vacuum is reduced to 4×10 -4 Pa or less. After establishing the sample coordinate system, writing field alignment and setting exposure parameters, the exposure begins. After the exposure is completed, the sample is taken out and developed. The exposed area is removed due to the increased solubility, leaving the unexposed photoresist as a mask. After development, the sample is placed on a hot plate and baked at a certain temperature and time to further solidify the electron beam glue and reduce the impact of moisture on subsequent processing.
[0142] In step F, first, a reactive ion etching (RIE) method is used to etch the amorphous Si down to a depth of about 400 nm along the electron beam glue mask window to form a mask window for etching the SiO2 thereunder; then, the RIE method is further used to etch the SiO2 down to a depth of about 850 nm along the amorphous Si mask window.
[0143] Step G, soak the sample in acetone for a period of time to remove the electron beam glue remaining on the surface; then, soak the sample in a potassium hydroxide solution with a concentration of about 20% for a certain period of time to remove the amorphous Si mask remaining on the surface; finally, rinse in pure water and ultrapure water for 1 minute each, blow dry the substrate surface with a nitrogen gun, and dry at 120°C for 30 minutes. After this step, SiO2 grooves are formed on the surface of the SiO2 / Si substrate.
[0144] Step H, using the steps shown in Example 1 of the present invention, successively growing Zn 0.79 Mg 0.21 O buffer layer and Zn with a thickness of about 1200nm 0.67 Mg 0.33 O electro-optical film.
[0145] Table 13. Chemical mechanical polishing process parameters of ZnMgO films
[0146] Polishing liquid pH value Pressure(g) Speed (rpm) Rate (nm / min) Time (minutes) 6.0 400 25 37 32
[0147] Step I, using the conditions shown in Table 13, chemical mechanical polishing (CMP) was performed on the sample surface to remove the Zn 0.67 Mg 0.33 The O electro-optical film was removed to form a smooth surface. Then, the substrate was rinsed in acetone, alcohol and pure water for 1 minute each, and the substrate surface was blown dry with a nitrogen gun and dried at 120°C for 30 minutes.
[0148] Step J: Using the PECVD method, a SiO2 upper confinement layer with a thickness of about 2000 nm is grown on the surface of the sample after CMP treatment.
[0149] Step K, spin-coating a photoresist with a thickness of about 7 μm on the surface of the sample at a rotation speed of about 3000 rpm. After coating, the sample is placed on a hot plate and baked at a certain temperature and time to stabilize the performance of the photoresist.
[0150] Step L, using a designed device separation photomask and a UV lithography machine for exposure, and then, through development and post-baking, obtaining a cured photoresist mask.
[0151] In step M, the SiO2 is etched downward along the photoresist window to a depth of about 5 μm by using the RIE method; then, the Si is further etched downward to a depth of about 100 μm by using the RIE method.
[0152] Step N, soak the sample in acetone for a period of time to remove the photoresist remaining on the surface; then, rinse in acetone, alcohol and pure water for 1 minute each, use a nitrogen gun to blow dry the substrate surface, and dry it at 120°C for 30 minutes; finally, use a dicing machine to scribe along the scribe lines formed on the substrate surface after step M to obtain discrete ZnMgO optical microring resonator devices.
[0153] Figure 6 This is the electron beam exposure layout of the ZnMgO micro-ring resonator device designed in Example 5 of the present invention. Figure 6In (a), the G values of the microring resonators from the first column to the fifth column on the left are 108.07nm, 158.07nm, 208.07nm, 258.07nm and 308.07nm respectively. In (a), the R values of the microring resonators from the first row to the third row on the top are 100.75μm, 201.5μm and 302.25μm respectively. Figure 6 As shown in (b)-(d), in order to make full use of the writing field space, each unit is composed of three micro-ring resonators. Figure 6 (e) is used for alignment. Figure 6 As shown in (e), at both ends of the bus waveguide, a wedge-shaped coupler with a length and tip width of approximately 300 μm and 300 nm, respectively, is used to couple with the optical fiber.
[0154] Figure 7 The Zn grown on the SiO2 / Si substrate in Example 5 of the present invention 0.67 Mg 0.33 XRD patterns of O films. 0.79 Mg 0.21 O buffer layer, these Zn 0.67 Mg 0.33 O films all showed (002) preferred orientation growth, and no significant phase separation between ZnO and MgO was found. 0.79 Mg 0.21 O buffer layer Zn 0.67 Mg 0.33 The half-height widths of the rocking curves of the (002) crystal plane of the O film are 7.59° and 2.79°, respectively. This indicates that the use of Zn 0.79 Mg 0.21 The O buffer layer significantly increases the Zn 0.67 Mg 0.33 O growth quality of electro-optical films.
[0155] Figure 8 The Zn before and after CMP treatment in Example 5 of the present invention 0.67 Mg 0.33 AFM image of the surface of the O film. After CMP treatment, the root mean square roughness of the film surface was reduced from 4.75±0.73nm to about 0.55±0.06nm. This shows that CMP significantly improves the flatness and smoothness of the sample surface. Figure 8 As shown in (a), Zn 0.67 Mg 0.33 The surface morphology of the O film is composed of secondary grains with a diameter of about 152.6±19.9nm. These secondary grains are formed by nano-sized grains. Figure 8As shown in (b), after CMP treatment, the secondary grains on the surface are destroyed and the grain diameter is reduced to 27.4±2.7nm.
[0156] Fig. 9 The macroscopic and local microscopic images of the ZnMgO micro-ring resonator device prepared in Example 5 of the present invention. Fig. 9 As shown in (a), a very close Figure 6 Design of the SiO2 trench array. Fig. 9 As shown in (b), the coupler end faces with upper width, lower width and height of 370nm, 243nm and 650nm are realized at both ends of the microring resonator. According to the relevant formula, based on the Zn with a width of 2250nm and a height of 850nm of the wedge-shaped coupler, 0.67 Mg 0.33 The coupling efficiency between the O-strip waveguide and the lens fiber with a Gaussian profile spot-size of about 2.2 μm can reach 46.7%. Fig. 9 As shown in (c) and (d), the slope of the SiO2 trench sidewall is as high as 87°, and a wurtzite structure Zn with a highly c-axis preferred orientation grows in the SiO2 trench. 0.67 Mg 0.33 O film.
[0157] Fig.10 are the performance parameters of the ZnMgO microring resonator prepared in Example 5 of the present invention. Fig.10 As shown in (a)-(c), the FSRs of the microring resonators with R = 100.75 μm, R = 201.5 μm, and R = 302.25 μm are 2.00 nm, 1.01 nm, and 0.68 nm, respectively, which are very close to the designed values. Fig.10 As shown in (d) and (e), the minimum half-width of the resonance peaks of the TE0 mode and TM0 mode of the R = 201.5μm microring resonator reaches 26pm and 29pm respectively. According to the relevant formula, the load quality factor of the TE0 mode and TM0 mode of the resonator reaches 0.59×10 5 and 0.54×10 5 , and thus their intrinsic quality factors (Q0) are approximately 1.18×10 5 and 1.08×10 5 , and using Al with a similar bandgap width 0.7 Sc 0.3 Optical microring resonator made of N electro-optical thin film (Q0≈3.6×10 4 ) is one order of magnitude higher than that of the 1.55μm wavelength. Furthermore, it is found that the optical transmission losses at 1.55μm wavelength are approximately 2.52dB / cm and 2.74dB / cm respectively. Fig.10As shown in (f), the energy coupling coefficient between the bus band of the R = 201.5 μm microring resonator and the microring gradually increases with the decrease of the coupling gap G, and the TM0 mode energy coupling coefficient is significantly greater than the TE0 mode energy coupling coefficient.
[0158] The Zn with a bandgap width of 3.97-5.33 eV prepared by the present invention 1-x Mg x O(0.33≤x≤0.74) electro-optical film and the silicon optical microring resonator based on the film can be applied to photonic devices such as electro-optic modulators, optical switches and electro-optical frequency combs in the ultraviolet-near infrared band, and have great application prospects in the fields of integrated photonics, nonlinear optics and optoelectronic fusion. The specific embodiments described above further explain the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. Wide bandgap Zn 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The preparation method comprises: Step A: Preparation of ZnMgO ceramic target; Step B: substrate cleaning; Step C: growing a ZnMgO thin film by radio frequency magnetron sputtering; Step D: atmospheric heat treatment of the ZnMgO film.
2. The wide bandgap Zn according to claim 1 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The optical bandgap of the ZnMgO film is 3.97-5.33 eV; the composition of the ZnMgO film is 0.33≤x≤0.74, where x represents the atomic ratio of Mg / (Zn+Mg); the electro-optic coefficient of the ZnMgO film is the Pockels effective electro-optic coefficient r along its c-axis direction. c or 33 , specifically: when x = 0.33, r c and r 33 are 8.12±0.25pm / V and 5.28±0.16pm / V respectively; when x=0.35, r c and r 33 are 5.16±0.03pm / V and 3.36±0.20pm / V respectively; when x=0.55, r c and r 33 are 5.02±0.43 and 3.27±0.28 pm / V respectively; when x=0.74, r c and r 33 They are 3.07±0.37pm / V and 2.00±0.24pm / V respectively.
3. The wide bandgap Zn according to claim 1 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The step A comprises: weighing raw materials according to the component ratio, preparing a method for growing wide bandgap Zn 1-x Mg x Ceramic targets for growing ZnO thin films and 0.79 Mg 0.21 Ceramic target for O buffer layer, 0.33≤x≤0.
74.
4. The wide bandgap Zn according to claim 1 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The step C includes: the process parameters of the radio frequency magnetron sputtering method include: when the background vacuum is reduced to 7.4×10 -7 When the pressure is below 300°C, a mixed gas of O2 and Ar is introduced into the growth chamber, the Ar / (Ar+O2) gas ratio is 50%-75%, the flow rate range is 5-10sccm, the substrate temperature range is 200-300°C, the gas pressure range is 2-5mTorr, the RF power range of the ceramic target is 100-150W, the distance range from the target to the substrate surface is 100-150mm, and the substrate rotation speed range is 15-30rpm.
5. The wide bandgap Zn according to claim 3 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The method for manufacturing a ceramic target comprises: using ZnO with a purity of 99.99% and MgO with a purity of 99.99% as raw materials, and manufacturing a target material according to a weight percentage of 91.6%-38.68%: 18.4%-61.32%; the Zn 0.79 Mg 0.21 The method for manufacturing an O buffer layer ceramic target comprises: using ZnO with a purity of 99.99% and MgO with a purity of 99.99% as raw materials, and manufacturing a target material according to a weight percentage of 89%:11%.
6. A wide bandgap Zn based on any one of claims 1-5 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The preparation method comprises: Step A, optical microring resonator layout design and fabrication; Step B, SiO2 / Si substrate cleaning; Step C, growing an amorphous Si mask; Step D, preparing electron beam gel and pre-baking; Step E, electron beam exposure, development, and post-baking; Step F, dry etching amorphous Si and SiO2 to form SiO2 grooves of a certain depth on the surface of the substrate; Step G, removing the amorphous Si mask and cleaning the substrate; Step H, using a radio frequency magnetron sputtering method to grow a c-axis preferentially oriented wide bandgap ZnMgO electro-optical film in the SiO2 groove; Step I, forming a smooth surface on the substrate surface through chemical mechanical polishing; Step J, growing a SiO2 upper confinement layer; Step K, spin coating photoresist and pre-baking; Step L, photolithography, development, and post-baking; Step M, deep etching of the SiO2 upper limiting layer and Si; Step N, removing the residual photoresist on the surface, cleaning the substrate and then scribing to form discrete ZnMgO optical microring resonators.
7. The wide bandgap Zn according to claim 6. 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized by: The ZnMgO optical microring resonator has an operating wavelength range of 250nm-2.5μm, covering a wide band from ultraviolet UVC to near infrared; it has a Pockels electro-optical modulation function, achieving 10 -18 Ultrafast response of the order of s; based on the device structure, it is further developed into electro-optic modulators, optical switches and electro-optic frequency comb photonic devices, which are applied in integrated photonics, nonlinear optics and optoelectronic fusion.
8. The wide bandgap Zn according to claim 6. 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The step A comprises: first, determining the width and height of the waveguide core layer for achieving single-mode transmission at the wavelength according to the target resonance wavelength of the device and the refractive index of the ZnMgO film; then, designing different microring radii R and bus waveguide-microring spacing G values according to the desired free spectral range FSR and taking into account possible process errors; finally, using dedicated software to prepare an electronic layout of an optical microring resonator array with different R and G.
9. The wide bandgap Zn according to claim 6. 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The step H comprises: using the preparation method of claim 1, successively growing Zn with a thickness ranging from 50 to 100 nm 0.79 Mg 0.21 O buffer layer and a wide bandgap ZnMgO electro-optical film whose thickness exceeds the depth of the SiO2 trench.
10. The wide bandgap Zn according to claim 6 1-x Mg x O (ZnMgO) electro-optical film preparation method, characterized in that: The chemical mechanical polishing treatment in step I includes: using a polishing liquid with a pH value of 5.55-6.46, performing chemical mechanical polishing treatment for a certain period of time under the conditions of a pressure range of 300-500g, a rotation speed range of 20-30rpm and a thinning rate of 30-60nm / min, removing the ZnMgO electro-optical film except in the SiO2 groove, and forming a smooth surface with a sub-nanometer root mean square roughness; then, rinsing in acetone, alcohol and pure water for 1 minute each, using a nitrogen gun to blow dry the substrate surface, and drying at 120°C for 30 minutes.